2022
DOI: 10.1002/clc.23791
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the plasma volume status of elderly patients with acute decompensated heart failure using bedside clinical, biological, and ultrasound parameters

Abstract: Objective: Assessment of intravascular volume status to ensure optimization before hospital discharge could significantly reduce readmissions. It is difficult to evaluate congestion on clinical signs during an episode of acute heart failure (ADHF) in elderly patients.Hypothesis: There is an association between various volume overload parameters in patients older than 75 years. Methods:We performed a single-center prospective longitudinal study of patients older than 75 years hospitalized for acute heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The main studies [21][22][23][24][25][26] evaluating approach based on volume status for the management of AHF and chronic HF are summarized in Table 2.…”
Section: Acute Heart Failure Management: Is a Change In The Approach ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main studies [21][22][23][24][25][26] evaluating approach based on volume status for the management of AHF and chronic HF are summarized in Table 2.…”
Section: Acute Heart Failure Management: Is a Change In The Approach ...mentioning
confidence: 99%
“…Leahova-Cerchez et al [21] Integrated approach based on clinical (JVD, HJR), biological and echocardiographic (IVC) signs of congestion may guide diuretic therapy, reducing the risk of renal failure in patients >75 years old with acute decompensated HF Khandwalla et al [24] Increasing IVC diameter, as demonstrated by ultrasound, is associated with increased risk for HF hospitalization and may be useful to manage patients.…”
Section: Acute Heart Failure Main Findings Chronic Heart Failure Main...mentioning
confidence: 99%